Efective Learning Form Afar: Optimizing Distance Learning During A Pandemic - Wilodati Wilodati (SOSIETAS, 2021)
The distance learning should be able to respond to the challenges of the 21st century which require students to have skills, knowledge and abilities in the fields of technology, media and information, learning skills and innovation. Such as the substantial problems that occur during learning at home are difficulty getting access and stable internet facilities, not having access to books with good reading levels, and other problems. This research uses systematic review method, meta-analysis. Through this research, various efforts can be found to make learning effective in a pandemic by improving 21st century skills. Hence, this research has implications for teachers to be able to understand various potential problems in learning and to see how alternative solutions to problems are so that educators are able to apply learning to be more effective and efficient.